Associations of Maternal Beliefs and Distress in Pregnancy and Postpartum With Breastfeeding Initiation and Early Cessation - Ritchie-Ewing, Genevieve (J Hum Lact, 2018)
BACKGROUND: Breastfeeding plays an important role in both maternal and infant health and well-being. While researchers have examined the relationship between postpartum psychological distress and breastfeeding behaviors, few have investigated links between prenatal distress, postpartum distress, and breastfeeding behaviors over time. RESEARCH AIM: We aimed to determine if prenatal breastfeeding beliefs and psychological distress during and after pregnancy were associated with initiation and early cessation rates of breastfeeding. METHODS: In our secondary data analysis, a nonexperimental longitudinal one-group design was used. We assessed pregnant women (N = 70) during four perinatal visits (early, mid, and late pregnancy and 7–10 weeks postpartum). Participants completed self-report surveys about psychological distress and depressive symptoms at each visit, breastfeeding beliefs during the third visit, and breastfeeding behaviors at the postpartum visit. RESULTS: Participants who breastfed for ⩾8 weeks had more positive beliefs about breastfeeding prior to delivery than participants with early cessation, who in turn had more positive beliefs than those who never initiated. Participants with early cessation reported heightened levels of pregnancy-specific distress in early pregnancy compared to those who continued breastfeeding or never initiated. Participants who continued breastfeeding for ⩾8 weeks reported less general anxiety and depressive symptoms in postpartum than those who discontinued or never initiated. CONCLUSIONS: Prenatal beliefs about breastfeeding, pregnancy-specific distress in early pregnancy, and general anxiety and depressive symptoms in postpartum are associated with breastfeeding initiation and continuation. Of clinical relevance, addressing prenatal and postpartum distress in the implementation of breastfeeding practice interventions could improve breastfeeding rates.